Epidemiological characteristics of COVID-19 patients treated at the Emergency Department of the Hospital Militar Central Luis Arias Schreiber - Pezo Dianderas, Katia Michelle (2021)
Objective: To determine the epidemiological characteristics of COVID-19 patients treated at the Emergency Department of the Hospital Militar Central Luis Arias Schreiber from July to October 2020. Materials and methods: A descriptive, observational and cross-sectional study was carried out with 89 patients who tested positive for SARS-CoV-2 on molecular and/or rapid tests. The information was collected from the daily progress report of the patients treated at the hospital’s Emergency Department from July to October 2020. The results were processed using the IBM SPSS Statistics V25.0. Results: Males were more likely to test positive for COVID-19 (84.27 %). Most cases occurred in patients aged between 50 and 59 (34.83 %). The highest percentage of deaths was found in patients older than 70 years, out of whom 71.43 % were females. Comorbidities were reported in patients aged 40 and older, out of whom 67.41 % had at least one of them. Obesity was the most frequent comorbidity, followed by hypertension and type 2 diabetes mellitus. Sixty-seven point four one percent(67.41 %) of the patients required non-invasive ventilation and most of them were hospitalized. Twenty-one point three four percent (21.34 %) of the patients required mechanic ventilation and 68.42 % were admitted to the intensive care unit. Conclusions: The most common characteristics of COVID-19 patients are male sex, ages between 50 and 59 years old, and obesity. Additionally, using non-invasive ventilation had a better prognosis than using mechanical ventilation.